2019
DOI: 10.1021/acs.est.8b06089
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Soil-Derived Carbon into Plants: Implications for Disposal of Nuclear Waste

Abstract: Radiocarbon ( 14 C) is potentially significant in terms of release from deep geological disposal of radioactive waste and incorporation into the biosphere. In this study we investigated the transfer of soil-derived C into two plant species by using a novel approach, where the uptake of soil-derived C into newly cultivated plants was studied on 8000-year leftover peat in order to distinguish between soil-derived and atmospheric C. Two-pool isotope mixing model was used to reveal the fraction of soil C in plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The exact mechanism causing this relationship is not obvious, but it may be due to increased uptake of soil 13 C in Plot 2m and Plot 3ac over 2017 to 2018. Previous studies have indicated that plants can take up to 5% carbon from the active soil reservoir 74 . In addition, changes in the biosynthetic pathways for each plant component as a response to marine biofertilisation may also play a part.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism causing this relationship is not obvious, but it may be due to increased uptake of soil 13 C in Plot 2m and Plot 3ac over 2017 to 2018. Previous studies have indicated that plants can take up to 5% carbon from the active soil reservoir 74 . In addition, changes in the biosynthetic pathways for each plant component as a response to marine biofertilisation may also play a part.…”
Section: Discussionmentioning
confidence: 99%
“…This connection highlights the need to consider the broader environmental impacts of radioactive discharge beyond the immediate concerns of radiotoxicity and marine ecosystem health. 11 The interplay of multiple environmental stressors can lead to synergistic effects, where the combined impact of different factors is greater than the sum of their individual effects. For instance, adding radiation stress to already stressed marine ecosystems can exacerbate the overall ecological impact.…”
Section: Radiation Risksmentioning
confidence: 99%
“…These isotopes can contribute to the formation of greenhouse gases like carbon dioxide (CO 2 ) and methane (CH 4 ), potent drivers of global warming. This connection highlights the need to consider the broader environmental impacts of radioactive discharge beyond the immediate concerns of radiotoxicity and marine ecosystem health . The interplay of multiple environmental stressors can lead to synergistic effects, where the combined impact of different factors is greater than the sum of their individual effects.…”
Section: Broader Environmental Focus and Radiation Risksmentioning
confidence: 99%
“…Tritium can be stored in organisms as tissue-free water tritium (TFWT) and organically bound tritium (OBT). , High-concentration tritium exposure activates microalgal cells’ reactive oxygen species (ROS) signaling pathway. It adversely affects cell growth and metabolism, while carbon-14 can quickly enter marine sediments and be absorbed by marine organisms. Marine ecosystems rely on microorganisms and microalgae to mediate carbon, nitrogen, phosphorus, sulfur, and pollutant degradation cycles. Therefore, tritium and carbon-14 pollution can have severe ecological risks in marine environments.…”
Section: Introductionmentioning
confidence: 99%